Cardiorespiratory Fitness of Police Recruits: Normative Reference Values and Temporal Trend. Issue 1 (31st January 2023) - Poirier, Sébastien; Houle, Julie; Lajoie, Claude; Trudeau, François
Abstract: Poirier, S, Houle, J, Lajoie, C, and Trudeau, F. Cardiorespiratory fitness of police recruits: normative reference values and temporal trend. J Strength Cond Res 37(1): 207–212, 2023—Several studies have highlighted the increased risk of cardiovascular diseases (CVDs) among police officers. Given the longitudinal association between cardiorespiratory fitness (CRF) in early adulthood and later appearance of CVD, the identification of police recruits exhibiting lower CRF could allow the implementation of targeted CVD prevention strategies. Unfortunately, norm-referenced values for the CRF of Canadian police recruits are not yet available. Thus, this research aimed to provide norm-referenced values for the CRF of police recruits in the province of Quebec (Canada) and to evaluate the temporal trend in the CRF of police recruits over a 14-year period. First, a model was developed to estimate maximal oxygen consumption (V̇O2 max) based on the results of the physical ability test (PAT) used for the recruitment of police officers in Quebec. Based on the previously developed model, the CRF of police recruits who completed the PAT from 2004 to 2017 was retrospectively assessed using administrative records. The analysis of 7, 234 PAT results including 2, 150 females (29.7%) and 5, 084 males (70.3%) suggests that police recruits generally present high levels of CRF with an average estimated V̇O2 max of 53.3 ml·min −1 ·kg −1 for males and 43.8 ml·min −1 ·kg −1 for females. Furthermore, our analyses showed significant but small positive correlations between estimated V̇O2 max and time periods of PAT performance for male ( r s = 0.105, p < 0.001) and female recruits ( r s = 0.125, p < 0.001). Overall, our results suggest that the CRF of police recruits in Quebec is considerably higher than that of their North American peers.